Trade Credit in Zimbabwean Manufacturing. - Fafchamps, M (1997)
Credit from supplies is an important but often neglected source of finance for manufacturing firms. Zimbabwe is no exception. Unlike credit from financial institutions, trade credit does not rely on formal collateral but on trust and reputation. Contract enforcement is flexible. Network effects and statistical discrimination affect the screening of trade credit applicants. Black entrepreneurs are disadvantaged by their lack of business contacts and by the difficulty of distinguishing themselves from the mass of financially insecure and short-lived African-owned businesses in Zimbabwe A vicious circle is created between weak financial base, unreliability as a debtor, and inability to gain access to credit.